Practical recommendations for considering culture, race, and ethnicity in personality psychology. Issue 2 (12th January 2022) - Arshad, Memoona; Chung, Joanne M.
Abstract: Personality science is the study of the individual. It aims to understand what makes people similar to others, different from some, and unique to themselves. However, there is room for research in personality to more thoughtfully consider culture, race, and ethnicity in order to better understand individual differences in people's patterns of thinking, feeling, and behaving. High impact personality journals rarely include such factors into the interpretation of results, and cross‐cultural and ethnic minority publications are limited within the discipline. This article offers a brief, non‐exhaustive overview of how culture, race, and ethnicity are examined in relation to personality, showing that: (1) social structures continue to be neglected in the research, (2) we can learn from research being conducted in neighboring areas, and (3) valuable work is already being done within personality psychology. We offer recommendations that emphasize community based participatory research methods, combined etic‐emic approaches, and contextualizing research findings to improve the consideration of culture, race, and ethnicity in personality research.